State Rubricator of Scientific and Myoma, Senior Reproductive Age and IVF/IVF+ICSI is there Any Connection? - M.M. Maksudova (Institute of Medico-legal Publications Pvt Ltd, 2020)
In women of older reproductive age, due to the physiological decrease in the ovarian reserve and morefrequent concomitant gynecological disorders, the effectiveness of the IVF/IVF-ICSI protocols is significantlyreduced, which is associated with a smaller number of obtained oocytes and low quality of embryos 5.